Prognostic value of androgen receptor expression in triple negative breast carcinomas: personal experience and comments on a review about “Triple-negative breast cancer: treatment challenges and solutions” by Collignon et al - Ieni A (Dove Medical Press, 2016)
Antonio Ieni,1 Valeria Barresi,1 Giuseppina Rosaria Rita Ricciardi,2 Barbara Adamo,3 Vincenzo Adamo,2 Giovanni Tuccari11Department of Human Pathology of Adult and Evolutive Age “Gaetano Barresi”, Section of Pathology, University of Messina, AOU “Policlinico G Martino”; 2Medical Oncology Unit AOOR Papardo-Piemonte, Department of Human Pathology of Adult And Evolutive Age “Gaetano Barresi”, University of Messina, Messina, Italy; 3Medical Oncology Hospital Clinic, Barcelona, SpainRecently, we read with great interest the review by Collignon et al entitled “Triplenegative breast cancer: treatment challenges and solutions”,1 which appeared in the last issue of Breast Cancer: Targets and Therapy. In this article, the authors extensively reviewed studies concerning the opportunity to identify triple negative breast carcinoma (TNBC) subtypes by newly proposed markers, taking into account their biological heterogeneity on the light of clinical implications.View original paper by Collignon et al.